Controllability of Nonlinear Neutral Fractional Integrodifferential Systems with Infinite Delay - Balachandran, K.; Divya, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we establish sufficient conditions for the controllability of neutral fractional integrodifferential systems with infinite delay and infinite neutral fractional systems with implicit derivative. Fixed point approaches are employed for achieving the required results. Examples are provided to illustrate the efficiency of the results.